University Education Policies in Nigeria: Challenges Preventing the Implementation and the Ways Forward - Ogunode Niyi Jacob; Ajape Temitope Solomon; Deborah Jegede (Pusat Studi Bahasa dan Publikasi Ilmiah, 2020)
This paper discussed the challenges preventing the implementation of University education policies in Nigeria. Secondary data were used in the papers. The secondary data were sourced from print materials and online journal and articles. The paper identified inadequate funding, inadequate infrastructural facilities, inadequate professional lectures, institutional corruption, lack of political will, insecurity challenge, political instability, poor policy formulation, strike actions, weak regulatory agencies and political influence as the challenges preventing effective implementation of Universities education policies in Nigeria. To address these challenges, the paper recommends the following; adequate funding of education, provision of adequate infrastructural facilities, fight institutional corruption, ensure adequate security in educational institutions, political officeholders should have positive political will towards implementation of higher education policies, employment of more professional teachers, implement agreed with different union groups, and political officeholders and school administrators should have political will to continue with educational policies on groups.